Cover Picture: Single‐Particle Spectroscopy of Alcohol‐to‐Olefins over SAPO‐34 at Different Reaction Stages: Crystal Accessibility and Hydrocarbons Reactivity (ChemCatChem 3/2014). Issue 3 (March 2014) - Qian, Qingyun; Ruiz‐Martínez, Javier; Mokhtar, Mohamed; Asiri, Abdullah M.; Al‐Thabaiti, Shaeel A.; Basahel, Suliman N.; Weckhuysen, Bert M.
<x xml:space="preserve">Abstract</x> Combine and shine The cover picture shows the concept of synchrotron‐based IR and UV/Vis microspectroscopy techniques monitoring the methanol‐to‐olefins reaction on a single SAPO‐34 crystal and the spatially resolved information obtained on the retained hydrocarbon species and crystal accessibility, as projected on the two screens. In their Full Paper on p. 772 ff., Q. Qian, J. Ruiz‐Martínez, B. M. Weckhuysen et al. applied in situ synchrotron‐based IR and UV/Vis microscopy in combination with isotopic switching experiments to identify the different hydrocarbon species formed and to assess the reactivity and accessibility of individual SAPO‐34 crystals. Major differences have been observed between the methanol‐to‐olefins and ethanol‐to‐olefins processes in terms of the number of reaction stages and the formation and activity of distinct hydrocarbon species, such as alkylated mono‐ and polyaromatics. The authors wish to thank Ella Marushchenko and Alexander Tokarev for the design of the cover image.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>